2022
DOI: 10.1002/jez.2589
|View full text |Cite
|
Sign up to set email alerts
|

The early acquisition of symbiotic algae benefits larval survival and juvenile growth in the coral Acropora tenuis

Abstract: Larval dispersal and postsettlement survival of corals play significant roles in the maintenance of coral populations. Most corals acquire their symbiotic algae (Symbiodiniaceae) from the environment in each generation (horizontal transmission). For horizontal transmitters, the quick establishment of symbiosis is important for their survival, since the photosynthetic activity of symbiotic algae provides energy.However, recent studies have indicated that oxidative stress resulting from photosynthesis might also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
1
7
1
Order By: Relevance
“…The lipid content of CF larvae was higher than that of SF larvae after fertilization, but there was no signi cant difference in survivorship between treatments under thermal stress conditions. In contrast with this nding, other studies have suggested that lipid levels in larvae may be associated with energy allocation in larvae (44) and the sizes of eggs and larvae (37), indicating that smaller eggs would have fewer energetic reserves (lipids) than larger eggs and larvae (18,36,37). Nevertheless, in this study, the lipid content of coral eggs was positively correlated with their survival rates, and the rate of lipid consumption was lower in SF larvae than in CF larvae under thermal stress after 21 d. Collectively, the stressed coral fragments produced smaller larvae, which were not vulnerable to thermal stress.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…The lipid content of CF larvae was higher than that of SF larvae after fertilization, but there was no signi cant difference in survivorship between treatments under thermal stress conditions. In contrast with this nding, other studies have suggested that lipid levels in larvae may be associated with energy allocation in larvae (44) and the sizes of eggs and larvae (37), indicating that smaller eggs would have fewer energetic reserves (lipids) than larger eggs and larvae (18,36,37). Nevertheless, in this study, the lipid content of coral eggs was positively correlated with their survival rates, and the rate of lipid consumption was lower in SF larvae than in CF larvae under thermal stress after 21 d. Collectively, the stressed coral fragments produced smaller larvae, which were not vulnerable to thermal stress.…”
Section: Discussioncontrasting
confidence: 98%
“…Egg volume (EV) was calculated using the formula EV = 4/3 πab 2 , where a=½ egg length and b=½ egg width. We also measured the amount of lipids in the eggs according to a previously described method (44).…”
Section: Physiological Parameters Of Coral Adultsmentioning
confidence: 99%
“…These results suggest the complex role of larval aggregation in shaping post-settlement performance of corals in response to ocean warming and acidification, and provide direct evidence for the benefits and tradeoff associated with coral chimerism in determining the recruitment success under future climate change. Uptake of algal symbionts and symbiosis establishment are of paramount importance to the early success and resilience of broadcast spawning corals (Suzuki et al, 2013;Yuyama and Higuchi, 2014;Hazraty-Kari et al, 2022), while this process is particularly susceptible to the ongoing ocean warming (Abrego et al, 2012;Yuyama et al, 2016;Yorifuji et al, 2017;Sun et al, 2020;Jiang et al, 2021;Williamson et al, 2021). Consistent with these aforementioned studies, our results also showed detrimental effects of heat stress on symbiont infection process, with symbiont infection rates being reduced by 50% at 30.5°C.…”
Section: Discussionsupporting
confidence: 89%
“…Evidence of symbiont contributions to the host energetics during early life stages are mixed. Some studies report extra energy reserves in symbiotic larvae (Harii et al, 2010; Hazraty‐Kari et al, 2022; Richmond, 1987) while other studies found little to no evidence of contributions from the symbiont (Hartmann et al, 2019; Kopp et al, 2016). Nevertheless, the host may control symbiont growth when resources are scarce or nearing metamorphosis by inducing cellular senescence, a permanently arrested but metabolically active state.…”
Section: Discussionmentioning
confidence: 99%
“…Symbiont selection by corals is influenced by multiple factors including host and symbiont genetic backgrounds, algal physiology and environmental availability (Abrego et al, 2009a; Coffroth et al, 2001; Cumbo et al, 2013; Little et al, 2004; Quigley et al, 2017; Yamashita et al, 2018). By acquiring symbionts, coral larvae may enhance survivorship and extend settlement competency periods, both of which play an important role in larval dispersal (Chamberland et al, 2017; Harii et al, 2009; Hazraty‐Kari et al, 2022; Suzuki et al, 2013; van Oppen et al, 2001). However, changes in the environment may alter the availability of symbionts, mechanisms controlling symbiont acquisition, or make combinations of some host and symbiont pairings less favourable (Abrego et al, 2012; Cunning et al, 2015; Howe‐Kerr et al, 2020; Winkler et al, 2015).…”
Section: Introductionmentioning
confidence: 99%